Aplikasi Sistem Informasi Pengelolaan Keuangan Dan Inventori Persediaan Barang Dengan Metode Perpectual Pada Ud. Sinar Sejahtera Berbasis Web - Nadiyah, Nadiyah; Arifin, Nur Hatima Indah (Fakultas Teknik, Universitas Wiraraja, 2023)
Analysis of goods inventory system is a sales information system that produces information that can be useful for supporting sales activities. Sales information system as an application that manages data in collecting, storing sales data so that it can be distributed back to the agency. Information system as a solution in overcoming UD Sinar Sejahtera in the process of managing sales data, purchase data, outgoing goods data, incoming goods data, stock data, and buyer data in an organized manner. The method used in developing this application uses the perpectual method which can be called the bookkeeping method, the results of feasibility testing from application users reach 83% if the application is feasible to use. This research produces new innovations and produces a financial and inventory management application system at CV Sinar Sajahtera Pondok Pesantren Nurul Jadid.